Relationship Between Financial Literacy and Academic Performance of Business Students in a Philippine Higher Education Institution - Aleli Mae A. Anda; Sushmita Sen L. Martinez; Nicholai G. Quiambao; Paulo V. Mendez; Mary Joan Antonette F. Rafon; Jesus Briones; Joanna Paula E. Verano (Research Synergy Foundation, 2026)
Effective financial literacy is critical for students in higher education institutions as it influences academic performance and overall success. This study examined the relationship between financial literacy and academic performance of business students in a Philippine higher education institution. A comprehensive quantitative-descriptive study was conducted with a sample of 172 Bachelor of Science in Business Administration (BSBA) students. A validated, researcher-developed questionnaire was distributed to the sampled respondents via Google Forms. Data analysis includes the use of percentages and frequencies, the weighted mean, and the Pearson correlation coefficient. The study disclosed that the respondents were mostly female BSBA students aged 21–23 in their fourth year, from low-income families with at least one parent who was at least high school-educated. While they demonstrated strong knowledge of financial concepts like budgeting, saving, investing, and credit, their financial behaviors and attitudes were inconsistent. BSBA students identified all the academic performance factors considered in the study as keys to their success. However, demographic factors showed no significant relationship with students’ financial literacy. On the other hand, the study revealed a significant relationship between financial literacy and academic performance. Based on these findings, the study proposes a financial literacy program to help BSBA students make informed financial decisions, increase academic engagement, and enhance personal development, ultimately leading to improved academic outcomes. This study reinforces that higher education institutions should implement financial literacy programs focused on practical financial management competencies, as these positively influence students' academic engagement and overall success.